Návrh marketingové strategie firmy - Židlíková, Eva (Vysoké učení technické v Brně. Fakulta podnikatelská, 2014)
Židlíková, E. Marketingová strategie firmy. Diplomová práce. Brno: Vysoké učení technické, 2014. Diplomová práce se zaměřuje na marketingovou analýzu brněnské cestovní kanceláře Victoria. Hlavním cílem je vytvoření marketingové strategie firmy na základě marketingového výzkumu a analýz, které zjišťují preference a zájmy spotřebitelů v cestovním ruchu. Práce je rozdělena na dvě části – teoretickou a praktickou. Teoretickou část tvoří kapitoly, ve kterých jsou zachycena různá teoretická východiska marketingu a postup tvorby marketingového plánu. V praktické části uvádím poznatky, týkající se samotné práce.

Židlíková, E. Corporate Marketing Strategy. Diploma Thesis. Brno: Brno University of Technology, 2014. The thesis focuses on a marketing analysis of the Victoria company, a travel agency located in Brno. Its principal objective is to create a corporate marketing strategy based on a marketing research and analyses that determine preferences and interests of consumers in the area of tourism. The thesis is subdivided into two sections – theoretical and practical. The theoretical section comprises chapters describing various theoretical bases of marketing as well as the manner of drafting a marketing plan. The practical section presents practical findings related to the thesis.
Marketing Strategy of the Company
Keywords: Marketingová strategie; marketingový mix; PESTE analýza; Porterova analýza; SWOT analýza; marketingový výzkum; Marketing strategy; marketing mix; PESTE analysis; Porter analysis; SWOT analysis; marketing research